Comparative investigations of biomass composition in differently managed grasslands of the Balaton Uplands National Park, Hungary - Magyar, Veronika; Penksza, Károly; Szentes, Szilárd (Gyepgazdálkodási Közlemények, 2021)
Phytosociological and biomass samples were collected in two territories of the Balaton Uplands National Park (Hungary) dominated by grassland habitats. Samples in the Tihany Peninsula had been taken in a pasture of Hungarian Grey Cattle. Studies were broadened to four areas of the Tapolcai Basin, Badacsonytördemic (undergrazed and overgrazed pastures, hayfield, control area). The areas were suitable for following up the changes of vegetation and production in every grazing season of a year. We evaluated the changes of species composition and ground cover, the measure of possible regeneration or degradation, and the changes of these factors from the viewpoint of feeding value. Covering rates of the grassland associations have doubled and species composition has improved in the Tihany Peninsula, however, forage value has not increased, due to the change in land use in favour of the natural area that is converting into grazing field. In case of the Taplocai Basin, low number of species (20 to 30) was detected in the undergrazed pasture and the control area. About one month per year grazing time in the undergrazed area was not enough to achieve a better state for species diversity, and the amount of forage remained high. The overgrazed pasture carries a low forage value and contains a high number of weed species, despite the spectacularly high total number of plant species (38 to 39), consequently, grazing pressure has to be decreased. Although the number of species is lower in the hayfield (26 to 28), species composition and ability for forage supply is much better, showing that the proper management of the area is taken here.